Leksyka z zakresu wróżbiarstwa i czarów w Nowym wielkim dykcjonarzu Pierre’a Daneta i Dymitra Franciszka Koli - Marczak , Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The paper aims to investigate Polish lexis belonging to the semantic fields of DIVINATION and WITCHCRAFT. The material was excerpted from the 18th-century trilingual Nowy wielki dykcjonarz (New grand dictionary). The semantic fields under analysis were divided into subfields. In the case of DIVINATION, the subfields of DIVINATION PRACTISES and PEOPLE FORETELLING THE FUTURE were identified. In turn, WITCHCRAFT was subdivided into MAGICAL PRACTICES, PEOPLE PRACTISING MAGIC and EFFECTS OF MAGIC. The analysis of the retrieved material suggests that the number of individual lexemes is relatively small and usually polysemic, which appears to contradict the popularity and prevalence of divination and witchcraft in the 18th-century Polish-Lithuanian Commonwealth as established by cultural historians. The supposed misrepresentation of the semantic fields under scrutiny may reflect the didactic nature of the Polish part of the dictionary.